Studies on Technological Problems Associated with the Processing of Cooked Frozen Prawns 1. Storage Conditions of Raw Material in Relation to Quality - IYER, T. S GOPALAKRISHNA; CHOUDHURI, D. R.; PILLAI, V. K. (Fishery Technology, 2025)
The chemical and organoleptic properties of prawn held inice for different days prior to cooking and the changes after freezingand. subsequent storage were studied with three different species ofprawn viz. Metapenaeus monoceros, Metapenaeus dobsoni andParapeneopsis stylifera. The optimum period for which the prawncan be kept under ideal conditions of icing prior to cooking has beenworked out.